The Influence of Digital Financial Reporting on Financial Transparency and Accountability in Public Companies - Rila Maufira (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The rapid advancement of digital technologies has transformed financial reporting practices and reshaped governance structures in public companies. This study aims to examine the influence of digital financial reporting on financial transparency and accountability, while also assessing the role of transparency as a key determinant of accountability in a digital reporting environment. Using a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS), the research analyzes companies that have integrated digital reporting systems, including XBRL-based disclosures, automated data processing, and real-time information access. The findings reveal that digital financial reporting significantly enhances financial transparency by improving disclosure quality, increasing information accessibility, and strengthening the timeliness of reporting. Furthermore, the results indicate that transparency plays a crucial role in promoting financial accountability through stronger oversight, improved data integrity, and greater managerial responsibility. These outcomes underscore that digitalization not only enhances reporting efficiency but also contributes to more robust governance mechanisms. The study highlights the need for technological readiness, managerial commitment, and regulatory reinforcement to support the effective adoption of digital financial reporting. Practical implications suggest that organizations should strengthen digital audit frameworks and enhance technological competencies to ensure that digital transformation continuously promotes transparency and accountability within the financial reporting ecosystem.